2013
DOI: 10.1002/jgrb.50139
|View full text |Cite
|
Sign up to set email alerts
|

Tectonic development of the Samail ophiolite: High‐precision U‐Pb zircon geochronology and Sm‐Nd isotopic constraints on crustal growth and emplacement

Abstract: [1] New high-precision single grain U-Pb zircon geochronology and whole rock Nd isotopic data provide insight into the magmatic and tectonic development of the Samail ophiolite. The analyzed rocks can be broadly divided into two groups based on their structural position, dates, and isotopic composition: an older group related to on-axis magmatism and a younger group of post-ridge dikes, sills, and stocks. Isotopic data suggest two distinct sources for the post-ridge magmas: five of the gabbros and tonalites fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
258
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 158 publications
(273 citation statements)
references
References 103 publications
15
258
0
Order By: Relevance
“…The age of the youngest zircon, 35.25 ± 0.15 Ma, is taken as the best estimate of the final crystallization age of the protolith of this sample. The small spread in ages seen in this sample is similar to those revealed by high precision U-Pb geochronology in the Samail ophiolite (44) and may be due to prolonged zircon crystallization in a replenished magma chamber or assimilation of slightly older wall rock.…”
Section: Age and Geochemistry Of The Palawan Ophiolite And Its Solesupporting
confidence: 74%
“…The age of the youngest zircon, 35.25 ± 0.15 Ma, is taken as the best estimate of the final crystallization age of the protolith of this sample. The small spread in ages seen in this sample is similar to those revealed by high precision U-Pb geochronology in the Samail ophiolite (44) and may be due to prolonged zircon crystallization in a replenished magma chamber or assimilation of slightly older wall rock.…”
Section: Age and Geochemistry Of The Palawan Ophiolite And Its Solesupporting
confidence: 74%
“…The high-grade metamorphism of the metamorphic sole can occur only at the inception of subduction because the hanging wall would subsequently be too cold to cause high-grade metamorphism (Wakabayashi and Dilek, 2003). Temporal and spatial relations of ophiolites and metamorphic soles have been well-documented in the Oman ophiolite by high-precision U-Pb zircon geochronology and whole rock Nd-isotopic data (Rioux et al, 2013;Warren et al, 2005). Warren et al (2005) reported coeval U-Pb zircon ages for trondhjemites (95.3±0.2 Ma) and for amphibolites (94.48±0.23 Ma), and suggested an SSZ origin for the Semail ophiolite.…”
Section: Discussionmentioning
confidence: 99%
“…Warren et al (2005) reported coeval U-Pb zircon ages for trondhjemites (95.3±0.2 Ma) and for amphibolites (94.48±0.23 Ma), and suggested an SSZ origin for the Semail ophiolite. However, Rioux et al (2013) provided more detailed U-Pb zircon ages and whole rock Nd isotopic data for the crustal rocks and the underlying metamorphic sole and concluded that most of the ophiolitic crust formed at an oceanic spreading center in <1 Ma in the Late Cretaceous, followed by subduction or thrusting that was established below the ophiolite after ≤0.25-0.5 Ma. Both mid-ocean ridge (MOR) and suprasubduction zone (SSZ) models have been proposed for the genesis of the Oman ophiolite (Rioux et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations